Family nursing care for a toddler with stunting and speech delay in Aceh Besar Regency - Aura Azahra Harahap; Yuni Arnita; Neti Hartaty; Syarifa Atika (PT WIM Solusi Prima, 2026)
Stunting and speech delay are health problems in toddlers that influence physical growth, cognitive development, and communication abilities. Inadequate management may negatively impact children’s long-term growth and development. The family plays a crucial role in prevention and management through adequate nutrition, developmental stimulation, and utilization of healthcare services. This final scientific paper aimed to describe the implementation of family nursing care for a toddler with stunting and speech delay. Based on the assessment conducted from December 30, 2025, to January 1, 2026, two priority nursing diagnoses were identified: inadequate nutritional intake (stunting) and delayed child development (speech delay). The interventions were designed on the five family health tasks. For the first diagnosis, the actions implemented included education on balanced nutrition using the ‘My Plate’ approach, demonstration of healthy menu planning, modification of the eating environment, and utilization of healthcare services. Interventions implemented for the second diagnosis included education on the importance of speech development stimulation, demonstration of language stimulation using flashcards and bibliotherapy, limitation of gadget use, and family assistance in decision-making regarding care and in the independent implementation of language stimulation at home. Evaluation results indicated improvements in the family’s knowledge, attitudes, skills, and self-confidence in caring for the child, as well as in fulfilling family health tasks. Community health centers are expected to enhance educational programs and family support initiatives to optimize child growth and development.